Using wireless sensor networks (WSN) for detecting leakage in water pipes - Bakar A.A.; Din M.M.; Yussof S.; Ghapar A.A.; Rusli M.E.; Chang G.C. (2023)
The leakage of underground water pipe used to provide water to every household will lead to great amount of water loss, money, and valuable resources and may cause public health risks. Leakage may occur at different places or components in water distribution network/system. Current techniques, which is acoustic leak detection system uses listening devices, leak noise correlators and tethered hydrophones. This technique requires a person to be on the field to perform investigation. This paper describes our prototype system using wireless sensor network (WSN) to detect water pipe leakages. The system consists of two major parts; the first part is the part that senses the leakage and the second part is the part that displays the required information on a graphical user interface (GUI) application running on a personal computer (PC). WSN is chosen because it can allow for remote access, can be left unattended for a long time after the deployment, suitable for hostile environments and can be deployed over a large geographical area.